Evaluation of the inhibition of culturable Enterococcus faecium, Escherichia coli, or Aeromonas hydrophilia by an existing drinking water biofilm. Issue 6 (3rd November 2008) - Meckes, Mark C; Scarpino, Pasquale V; Green, Christopher F; Ortiz, Melchor; Gibbs, Shawn G
Abstract : Biofilms in potable water distribution systems consist of microorganisms that can survive and grow under the low nutrient concentrations commonly found within water distribution systems. This experiment evaluated the ability of an existing biofilm to reduce the number of introduced microorganisms adhered to materials in an aquatic environment. Ductile iron biofilm sampling coupons were separated into two groups, one had existing biofilm (pre-colonized) and the second group of coupons had no biofilm present (control). Biofilm sampling coupons were challenged by suspensions of individual study organisms consisting of Enterococcus faecium, Escherichia coli, or Aeromonas hydrophilia, and a sterile solution (control). Densities of culturable study organisms on control coupons were compared to densities of these same culturable organisms on biofilm pre-colonized coupons. Results demonstrate that drinking water distribution systems may be vulnerable to the development of potentially pathogenic bacteria in biofilm when lines are initially placed in service. Conclusions are that existing biofilm may serve as a barrier to introduced study organisms.